Dynamics of Family Law in the Context of Globalization: Comparison Between Legal Systems - Achen Karriel (ILAW, 2025)
The dynamics of family law have experienced significant transformation in the era of globalization, driven by the increasing influence of international norms, transnational interactions, and the growing emphasis on human rights. This study aims to analyze the reform of family law across different legal systems through a comparative legal approach, focusing on how globalization shapes legal frameworks, principles, and practices. The research employs a normative legal method with statutory, conceptual, and comparative approaches, relying on secondary data obtained from legal documents and academic literature. The findings reveal that globalization encourages the convergence of family law systems, particularly in the adoption of human rights principles such as gender equality, child protection, and individual autonomy. However, the study also identifies persistent divergence due to cultural, religious, and social factors, especially in regions where legal pluralism remains strong. While European legal systems tend to exhibit greater harmonization through supranational institutions, many Asian systems demonstrate selective adaptation by integrating global norms with local values. The study concludes that an effective model of family law reform requires a balanced approach that combines universal legal standards with socio-cultural sensitivity, ensuring both legal certainty and social legitimacy in the globalization era.